Cortical and Subcortical Neural Correlates for Respiratory Sensation in Response to Transient Inspiratory Occlusions in Humans - Chan, Pei-Ying S.; Cheng, Chia-Hsiung; Wu, Yu-Ting; Wu, Changwei W.; Liu, Ho-Ling A.; Shaw, Fu-Zen; Liu, Chia-Yih; Davenport, Paul W. (Frontiers in Physiology, 2018)
Cortical and subcortical mechanosensation of breathing can be measured by short respiratory occlusions. However, the corresponding neural substrates involved in the respiratory sensation elicited by a respiratory mechanical stimulus remained unclear. Therefore, we applied the functional magnetic resonance imaging (fMRI) technique to study cortical activations of respiratory mechanosensation. We hypothesized that thalamus, frontal cortex, somatosensory cortex, and inferior parietal cortex would be significantly activated in response to respiratory mechanical stimuli. We recruited 23 healthy adults to participate in our event-designed fMRI experiment. During the 12-min scan, participants breathed with a specialized face-mask. Single respiratory occlusions of 150 msec were delivered every 2-4 breaths. At least 32 successful occlusions were collected for data analysis. The results showed significant neural activations in the thalamus, supramarginal gyrus, middle frontal gyrus, inferior frontal triangularis, and caudate (AlphaSim corrected p < 0.05). In addition, subjective ratings of breathlessness were significantly correlated with the levels of neural activations in bilateral thalamus, right caudate, right supramarginal gyrus, left middle frontal gyrus, left inferior triangularis. Our results demonstrated cortical sources of respiratory sensations elicited by the inspiratory occlusion paradigm in healthy adults were located in the thalamus, supramarginal gyrus, and the middle frontal cortex, inferior frontal triangularis, suggesting subcortical and cortical neural sources of the respiratory mechanosensation are thalamo-cortical based, especially the connections to the premotor area, middle and ventro-lateral prefrontal cortex, as well as the somatosensory association cortex. Finally, level of neural activation in thalamus is associated with the subjective rating of breathlessness, suggesting respiratory sensory information is gated at the thalamic level.